IMPROVING STUDENTS' SPEAKING ABILITY BY USING THE PROBLEM BASED LEARNING (PBL) AT SMP SWASTA HARVARD MARTUBUNG - Pardosi, Masta Sarina; Swondo, Ashari P. (Universitas Potensi Utama, 2021)
The objective of this study is to investigate whether the application of Problem Based Learning (PBL) Improves the students’speaking ability at SMP Swasta Harvard Martubung. The study was conducted by using classroom action research. The subject of this research was the eight grade students’ of SMP Swasta Harvard Martubung which consisted of 44 students. The research was conducted in two cycles. The first cycles consisted of three meetings and the second cycle consisted of three meetings. The instrument for collecting the quantitave data was essay test for reading and the instrument for collecting qualitative data was interview, observation sheet, questionnaire, and diary notes. Based on the analysis, students’ speaking ability is improved in every test. In test I, The mean score was 59. In test II in cycle I, the mean score was 75.04, and in the test III in cycle II the mean score was 82.11. Based on the observation sheet, diary notes, and interview sheet, it was found that the teaching learning process ran well, the students more active, enthusiastic in working in group. It was concluded that Problrm Based Learning can improve the students’ speaking ability.